Preparing for patient partnership: A scoping review of patient partner engagement and evaluation in research - Marissa Bird; Carley Ouellette; Carly Whitmore; Lin Li; Kalpana Nair; Michael H. McGillion; Jennifer Yost; Laura Banfield; Elaine Campbell; Sandra L. Carroll (Wiley, 2020)
Abstract Background Realizing patient partnership in research requires a shift from patient participation in ancillary roles to engagement as contributing members of research teams. While engaging patient partners is often discussed, impact is rarely measured. Objective Our primary aim was to conduct a scoping review of the impact of patient partnership on research outcomes. The secondary aim was to describe barriers and facilitators to realizing effective partnerships. Search Strategy A comprehensive bibliographic search was undertaken in EBSCO CINAHL, and Embase, MEDLINE and PsycINFO via Ovid. Reference lists of included articles were hand‐searched. Inclusion Criteria Included studies were: (a) related to health care; (b) involved patients or proxies in the research process; and (c) reported results related to impact/evaluation of patient partnership on research outcomes. Data Extraction and Synthesis Data were extracted from 14 studies meeting inclusion criteria using a narrative synthesis approach. Main Results Patient partners were involved in a range of research activities. Results highlight critical barriers and facilitators for researchers seeking to undertake patient partnerships to be aware of, such as power imbalances between patient partners and researchers, as well as valuing of patient partner roles. Discussion Addressing power dynamics in patient partner‐researcher relationships and mitigating risks to patient partners through inclusive recruitment and training strategies may contribute towards effective engagement. Further guidance is needed to address evaluation strategies for patient partnerships across the continuum of patient partner involvement in research. Conclusions Research teams can employ preparation strategies outlined in this review to support patient partnerships in their work.